Analisis pengaruh financial leverage dan operating leverage terhadap stock return - As'ad Syaifullah (INOVASI, 2018)
This study aimed to examine the effect of financial leverage and operating leverage on stock return. The population of this study were 135 industrial manufacturing company listed on the Indonesia Stock Exchange (IDX) with a sample of 11 companies during the years 2011-2015. This study used purposive sampling method. The data analysis technique used in this study is multiple regression analysis. The results of this study concluded that concludes that the financial leverage and operating leverage no significant effect on stock return. While partially operating leverage effect on stock return, but no effect of financial leverage on stock return.